Subjective visual vertical after treatment of benign paroxysmal positional vertigo - Ferreira, Maristela Mian [UNIFESP] (2017)
Introduction: Otolith function can be studied by testing the subjective visual vertical, because the tilt of the vertical line beyond the normal range is a sign of vestibular dysfunction. Benign paroxysmal positional vertigo is a disorder of one or more labyrinthine semicircular canals caused by fractions of otoliths derived from the utricular macula. Objective: To compare the subjective visual vertical with the bucket test before and immediately after the particle repositioning maneuver in patients with benign paroxysmal positional vertigo. Methods: We evaluated 20 patients. The estimated position where a fluorescent line within a bucket reached the vertical position was measured before and immediately after the particle repositioning maneuver. Data were tabulated and statistically analyzed. Results: Before repositioning maneuver, 9 patients (45.0%) had absolute values of the subjective visual vertical above the reference standard and 2 (10.0%) after the maneuver; the mean of the absolute values of the vertical deviation was significantly lower after the intervention (p < 0.001). Conclusion: There is a reduction of the deviations of the subjective visual vertical, evaluated by the bucket test, immediately after the particle repositioning maneuver in patients with benign paroxysmal positional vertigo. (C) 2016 Associacao Brasileira de Otorrinolaringologia e Cirurgia Cervico-Facial. Published by Elsevier Editora Ltda.